Palaeocurrents and Provenance: Uplift History of the Meratus Complex, SE Kalimantan - Duncan Witts (Berita Sedimentologi, 2013)
The Barito Basin in southeast Kalimantan contains a thick sedimentary succession of Middle Eocene to Pleistocene age. The basin is separated from the much smaller Asem-Asem Basin by the Meratus Mountains – a complex of metamorphosed arc and ophiolitic rocks that record the accretion of East Java-West Sulawesi to Sundaland in the mid-Cretaceous. The complex was later uplifted during the Neogene. The uplift had a profound effect on the basin architecture, developing a foredeep along the emerging mountain front, and creating the present-day hydrocarbon plays of the basin. Thus, understanding the history of the Meratus uplift not only provides insight into the tectonic evolution of the basin, but also the development of the hydrocarbon system. Previous estimates of the age of uplift range from Middle Miocene to Late Miocene. Consequently, linking the uplift to regional tectonics has remained speculative. This article gives a very brief summary of palaeocurrent and provenance data, and makes reference to palynology results, that collectively aid our understanding of the Meratus uplift. The data were collected along the western flank of the Meratus Mountains during field and provenance studies between 2009 and 2011, as part of a PhD at Royal Holloway University, London. Additional data were collected during recent fieldwork with BP Indonesia, in association with Institut Teknologi Bandung (ITB), Indonesia.